ІЛЕ ӨЗЕНІ БОЙЫНДАҒЫ ТОҒАЙЛАРДАҒЫ АҒАШ ЖƏНЕ БҰТА ЖАРТЫЛАЙ ҚАТТЫҚАНАТТЫЛАР (Heteroptera) ФАУНАСЫНА (Experimental biology, 2015)
As a result, studies of floodplain riparian woodlands of the river Ili identified 42 species from 8 families Heteroptera. Among them zoophages – 9 zoofitofagi – 7, the remaining 26 species – phytophagous.
Keywords: river Ili; zoophages; zoofitofagi; phytophagous